An herbaceous-shrub flora under prescribed fire in a Brazilian Cerrado - Naves da Silva Rios, Mary; Sousa-Silva, José Carlos; Klink, Carlos Augusto (Revista de Ciências Agro-Ambientais, 2021)
Monitoring of vegetation on the herbaceous layer in a Cerrado sensu stricto in Planaltina (DF) was carried out eight times from 1988 to 1994 and in 2012, in two areas of 1.25 ha (Area 1, Area 2). Using the interception method on line, two transections of 100 m in length were defined, which were subdivided in sample units measuring one meter, totaling 200 units per area. In Area 1, prescribed burnings were applied in 1988, 1990 and in 1992. Area 2 was protected until July 1994, however an accidental fire hit the whole area in August the same year. Species of different habits up to a meter high were recorded in both areas. A number ranging between 92 and 134 species was observed from 1988 to 1994, and 115 species were recorded in 2012 in Area 1. Also, a number between 97 and 129 species was observed from 1988 to 1994, and 106 species were recorded in 2012 in Area 2. The results indicated the recovery and resiliency of the community after biennal burnnings. Biennal prescribed fires did not change the richness and diversity, but the community structure. The suppression of fire for 18 years did not promoted differences in the richness, but in the community diversity and structure. The exclusion of fire for 18 years also did not favored the floristic similarity between the two areas.